Effect of muscle type and frozen storage on the quality parameters of Iberian restructured meat preparations. (October 2014) - Antequera, Teresa; Pérez-Palacios, Trinidad; Rodas, Elena; Rodríguez, Mar; Córdoba, Juan J
The main objective of this study was to evaluate the effect of muscle type and frozen storage on the quality of restructured meat preparations from undervalued Iberian muscle to make use of meat from a high-quality and natural pig production system. The effect of two muscle types (i.e. white-glycolytic (W) and red-oxidative (R)) and frozen storage (lasting 0, 30, 60 and 90 days) on quality characteristics were assessed. Significant differences were found between the W and R Iberian restructured preparations in most physicochemical and some colour, texture and sensory traits, and in the fatty acid profile and oxidative measurements, suggesting that the R muscles are more suitable; however, the microbial contamination should be reduced. Frozen storage reduced but did not eliminate the initial microbial contamination, and it enhanced some quality traits in the Iberian restructured preparations, i.e. increased a* values, cohesiveness and juiciness and decreased adhesiveness and pastiness, without negatively affecting any parameter. Thus, frozen Iberian restructured preparations are recommended to be commercialized. In addition, the implementation or revision of Hazard Analysis and Critical Control Point is recommended to reduce microbial contamination.